AN ANALYSIS OF APOLOGY USED BY THE FIRST SEMESTER OF ENGLISH DEPARTMENT STUDENTS OF UNRIKA - Sri Sugiharti (JURNAL DIMENSI, 2013)
This study focuses on the apology used by the English Department Students of unrika, Batam. Te sample can be taken 10 %-15%. So, in this study the writer takes 10 % of the total population. So, the number of sample is 16 students as the respondents of this study .The use of “excuse” is most often used in saying when they come late 56,25%, then use of “sorry” is most frequently used when the respondents do not come to campus. The use of sorry is most often used when the respondents do not assigment75 %. So, the use of “sorry” is the most frequently used in saying of apology